„Sit tibi terra levis” - MARCU, Felix (Studia Universitatis Babeș-Bolyai Historia, 2016)
2013 was the year in which archaeology has lost several specialists who have dedicated their whole life to its practice. Not only this scientific field, but also their family, which included numerous friends, colleagues, admirers and foes, even the latter regarding them with the due respect. Their loss is as tragic as it is unexpected. All were senior researchers recognized nationally and internationally. The first was Alexandru Suceveanu, followed by Dan Isac, Dorin Alicu and Nubar Hamparţumian. They were not alone, surrounded by friends and many people they have taught this very special craft to.